GERENCIAMENTO DE PROGRAMAS DE AUDITORIA VISANDO A CERTIFICAÇÃO DE SISTEMAS DE GESTÃO INTEGRADA (SGI) - UM ESTUDO SOBRE A APLICAÇÃO DA NORMA ISO 19011:2002 - Pimenta, Luiz Carlos Pacheco (2007)
A survey about external certification audit programmes. It testifies that the Sustainable Development concept has a strong influence in organization's management. It introduces the Integrated Management Systems based on ISO 9001, ISO 14001 and OHSAS 18001 standards as the organizations puts in practice this concept. It discusses the external certification as a form to improve the trustiness in those Systems. It testifies that external certification process is based in the results of audits carried out by Certification Bodies in accordance with complex audit programmes. It suggests managing these programmes in accordance with the guidelines of clause 5 of ISO 19011 standard. It proposes making sure how much those guidelines are applicable to Certification Body's activities by a study case. It introduces a questionnaire applied in a Certification Body with results obtained by interviews and documents reviews. It checks that 96.9% of the guidelines are applicable to the organization, of those 68.2% has been established and presents possible solutions to establish the remainder 31.8%. It concludes at this moment the audit programme is appropriate to the business of the organization and presents comments for appreciation of the Certification Body to improve its audit programme. It concludes the results are either applicable to internal and supply chain evaluation audits programmes